Impacto del uso de las facturas negociables en el desarrollo productivo de las empresas en Perú: 2015-2023 - Broncano Seminario, Marlon Abel (2024)
Business financing is essential for the creation, expansion, and sustainability of companies. However, many businesses face significant challenges in accessing formal financing. In 2023, only 28.7% of companies registered with SUNAT had access to the formal financial system. In this context, alternative sources, such as negotiable invoices, have emerged and are transforming the Peruvian financial landscape. This research analyzes the impact of negotiable invoices on the productive development of Peruvian companies during 2015-2023, using a quasi-experimental approach based on the difference-in-differences (DiD) method. The key variables analyzed were survival, access to credit, sales, and employment, utilizing data from official sources such as SUNAT, SBS, and CAVALI. The results show that companies using negotiable invoices significantly improved their survival probability. Although the use of negotiable invoices favored short-term access to credit, this effect diminished over time. Regarding sales and employment, mixed impacts were observed: in the short term, there were negative effects, but companies that continuously used negotiable invoices experienced positive improvements, particularly among micro and small enterprises. In conclusion, the use of negotiable invoices has a relatively positive impact on the productive development of Peruvian companies, although challenges remain in assessing their overall impact.